Exosomal crosstalk: the metastatic language of hepatocellular carcinoma - Xu, Qian; Chen, Jinhan; Liu, Yi; Yu, Jinsheng; Zhao, Fangmin; Shu, Qijin (Frontiers in Immunology, 2026)
Exosomes have garnered considerable attention in hepatocellular carcinoma (HCC) research owing to their critical function in regulating intercellular communication within the tumor microenvironment. Their inherent composition, structural integrity, and cargo-specific properties underpin critical functions in orchestrating cellular information transfer. This review delineates the fundamental biology of exosomes, their multifaceted pathophysiological roles in HCC, and the inherent translational promise of exosome-based therapeutic platforms for HCC management. Emerging evidence positions exosomes as dual-functional entities in HCC: not only propagating tumor progression and metastasis but also emerging as liquid biopsy-based diagnostic indicators for early detection and prognostic stratification, as well as nanoscale delivery platforms for site-specific therapeutic payloads. Nevertheless, despite growing recognition of exosomal functions in HCC, the precise mechanisms governing their functional duality and clinical translatability demand further elucidation. Through critical appraisal of extant literature, this review delineates actionable research priorities to catalyze mechanistic dissection and accelerate bench-to-bedside translation in exosome-based HCC management.